263 Heads up for youth sport concussion: moving from awareness to evaluation of behavioural intention. (1st September 2016) - Sarmiento, Kelly; Lee, Robin; Dellinger, Ann; Baldwin, Grant
Abstract : Background: Children and adolescents account for an estimated 65% of emergency department visits for sports and recreation-related traumatic brain injuries, including concussions. Immediate identification and appropriate response to a concussion can help reduce the risk of short- or long-term health problems that can affect thinking, learning, behaviour, and/or emotions. Description of the Problem: Combining innovative and evidence-based communication strategies, CDC created HEADS UP. HEADS UP is a series of educational initiatives grounded in audience preferences for content, design, format, and distribution channels. The content is specifically built to draw attention to what was considered an under-reported and under-identified public health problem and is designed to improve awareness, early identification and management of sports-related concussion. Results: In the last decade, CDC's HEADS UP has partnered with over 85 organisations, received over 200 million media impressions, distributed more than 6 million print resources, and obtained over 40 million social-media impressions. In addition, through HEADS UP, CDC has trained over 3 million sports coaches and health care professionals through online training courses required by many state policies and sports programs. Evaluation results indicate improvements in knowledge and attitudes towards concussion after exposure to HEADS UP materials. Conclusion: CDC's HEADS UP demonstrates how a health communication initiative can play a critical role in driving the science of an important health issue and can help support implementation of policies on a large-scale. As CDC embarks on the next stage of HEADS UP, continued emphasis will be placed on adapting to the changing landscape of concussion research and awareness and identifying effective approaches for improving both behaviours and the culture of concussion nationwide.